Differentiated approach to assessing students’ academic achievements - Есингельдинов, Бауржан; Аширбаев, Нургали; Исмаилова, Гульдана; Сарсекенов, Рауан; Сабырханова, Перизат (Pedagogy and Psychology, 2021)
The article highlights a brief analysis of trends in education, a review of Kazakhstani and foreign teachers’ studies in the field of applying differentiated approach in teaching and students’ academic achievement assessing system in recent years. The effectiveness of applying differentiated approach in the context of the current criteria assessment system is shown. The importance of the teacher’s role in the application of differentiation in assessment is noted. The results of surveying secondary schools teachers of mathematics are presented. "Pearson’s chi-square criterion" method was used to analyze the results of the survey. Conclusions are drawn based on the results of the study.